Leadership : theory, application, skill development - Lussier, Robert N.; Achua, Christopher F. (Cincinnati, OH : South-Western College, 2001)
This book is about: Individuals as leaders; Team leadership; Organizational leadership; ...
Keywords: Leadership; Workplace; Leadership; Teams in the workplace